Question Analysis in 11th Grade Chemistry Book in Term of Critical Thinking Indicators - Imam Sri Nugroho; Sri Mulyani; Elfi Susanti (PAEDAGOGIA, 2021)
This study aims to determine the indicators of critical thinking skills that developed in the questions that contained in the XI grade high school chemistry textbook and to determine the critical thinking level of the questions developed in the XI high school chemistry textbook. This study is a qualitative research using descriptive documentation analysis method or content analysis. The document that analyzed are questions in the chemistry textbook used by eleventh grade students at four Senior High Schools in Surakarta. The sampling technique that used is multistage sampling and data validation using observer triangulation. The results showed that the critical thinking indicators that appeared on the questions from the textbooks analyzed included basic clarification, appearing at 100%; bases for a decision appearing at 0%; inference appearing at 88.9%; Advanced clarification appearing at 38.9%; supposition and integration appearing at 31.5%; auxiliary ability appearing at 40.7%. Meanwhile, based on the Critical Thinking Level (TBK), the questions included in the TBK 0 group are 0%; TBK 1 are 29.6%; TBK 2 are 68.5%; TBK 3 are 1.8%.